New species of Hercostomus Loew, 1857 (Dolichopodidae, Diptera) from Japan - Negrobov, O.p.; Kumazawa, T.; Tago, T.; Sato, M. (Zootaxa, 2016)
Six new species of the genus Hercostomus Loew, 1857, are described from Japan: Hercostomus acutiformis Negrobov, Kumazawa & Tago sp. nov., H. falcilis Negrobov, Kumazawa & Tago sp. nov., H. flavipalpus Negrobov, Kumazawa, Tago & Sato sp. nov., H. nigricollaris Negrobov, Kumazawa & Tago sp. nov., H. spathulatus Negrobov, Kumazawa, Tago & Sato sp. nov., H. spinitibialis Negrobov, Kumazawa & Tago sp. nov. Hercostomus flaveolus Negrobov & Chalaya, 1987 is newly recorded from Japan, and Hercostomus arcticus Yang, 1996 is newly synonymized with Hercostomus flaveolus (syn. nov.). The holotype of Hercostomus flaviventris Smirnov & Negrobov, 1979 is redescribed. Hercostomus ussurianus Stackelberg is transferred to the genus Gymnopternus Loew, 1857 (stat. nov.). A key to the eleven recognized species of Japanese Hercostomus is provided.